Atrial Cardiopathy and the Risk of Ischemic Stroke in the CHS (Cardiovascular Health Study). Issue 4 (April 2018) - Kamel, Hooman; Bartz, Traci M.; Elkind, Mitchell S.V.; Okin, Peter M.; Thacker, Evan L.; Patton, Kristen K.; Stein, Phyllis K.; deFilippi, Christopher R.; Gottesman, Rebecca F.; Heckbert, Susan R.; Kronmal, Richard A.; Soliman, Elsayed Z.; et al.
Abstract : Background and Purpose—: Emerging evidence suggests that an underlying atrial cardiopathy may result in thromboembolism before atrial fibrillation (AF) develops. We examined the association between various markers of atrial cardiopathy and the risk of ischemic stroke. Methods—: The CHS (Cardiovascular Health Study) prospectively enrolled community-dwelling adults ≥65 years of age. For this study, we excluded participants diagnosed with stroke or AF before baseline. Exposures were several markers of atrial cardiopathy: baseline P-wave terminal force in ECG lead V1, left atrial dimension on echocardiogram, and N terminal pro B type natriuretic peptide (NT-proBNP), as well as incident AF. Incident AF was ascertained from 12-lead electrocardiograms at annual study visits for the first decade after study enrollment and from inpatient and outpatient Medicare data throughout follow-up. The primary outcome was incident ischemic stroke. We used Cox proportional hazards models that included all 4 atrial cardiopathy markers along with adjustment for demographic characteristics and established vascular risk factors. Results—: Among 3723 participants who were free of stroke and AF at baseline and who had data on all atrial cardiopathy markers, 585 participants (15.7%) experienced an incident ischemic stroke during a median 12.9 years of follow-up. When all atrial cardiopathy markers were combined in 1 Cox model, we found significant associations with stroke for P-wave terminal force in ECG lead V1 (hazard ratio per 1000 μV*ms 1.04; 95% confidence interval, 1.001–1.08), log-transformed NT-proBNP (hazard ratio per doubling of NT-proBNP, 1.09; 95% confidence interval, 1.03–1.16), and incident AF (hazard ratio, 2.04; 95% confidence interval, 1.67–2.48) but not left atrial dimension (hazard ratio per cm, 0.96; 95% confidence interval, 0.84–1.10). Conclusions—: In addition to clinically apparent AF, other evidence of abnormal atrial substrate is associated with subsequent ischemic stroke. This finding is consistent with the hypothesis that thromboembolism from the left atrium may occur in the setting of several different manifestations of atrial disease. Abstract : Supplemental Digital Content is available in the text.